1988
DOI: 10.1007/bf00975001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and physical abuse in the schools: A paradigm for understanding post-traumatic stress disorder in children and youth

Abstract: The literature on Post-Traumatic Stress Disorder (PTSD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…For example, children abused in educational settings may be left with feelings of shame, worthlessness, confusion, and guilt (Dolmage, 1995). They may also experience PTSD or related symptoms, including avoidance of school and fear associated with educators; loss of trust in or fear of adults, especially educators; loss of interest in school; denial of or refusal to discuss the traumatic event; nightmares; and excessive crying (Hyman et al, 1988). As parents, survivors may be retraumatized when they send their children to school, fearing that they, too, will be victimized.…”
Section: Factors Contributing To Harmmentioning
confidence: 99%
“…For example, children abused in educational settings may be left with feelings of shame, worthlessness, confusion, and guilt (Dolmage, 1995). They may also experience PTSD or related symptoms, including avoidance of school and fear associated with educators; loss of trust in or fear of adults, especially educators; loss of interest in school; denial of or refusal to discuss the traumatic event; nightmares; and excessive crying (Hyman et al, 1988). As parents, survivors may be retraumatized when they send their children to school, fearing that they, too, will be victimized.…”
Section: Factors Contributing To Harmmentioning
confidence: 99%
“…Some studies have demonstrated more traumatic reactions in younger children (e.g. Hyman, Zelikoff & Clarke, 1988;Rigamer, 1986), while others have failed to find age effects (e.g. Pynoos et al, 1987;Terr, 1979).…”
mentioning
confidence: 96%
“…Identification of the constellation of symptoms associated with traumatic abuse is essential if treatment is to be effective (Hyman, Zelikoff, & Clarke, 1988). For example, a client, Pat (not her real name), a victim of repetitive, unpredictable physical and sexual abuse by several members of her family, had been in psychiatric treatment facilities for over seven years, yet had not been treated for the sequelae of sexual abuse.…”
Section: Issues In Residential Treatmentmentioning
confidence: 99%